Effects of cinnamon (Cinnamomum zeylanicum) bark oil on testicular antioxidant values, apoptotic germ cell and sperm quality - Yüce, A; Türk, G; Çeribaşı, S; Sönmez, M; Çiftçi, M; Güvenç, M (My University, 2013)
Cinnamon and its contents have multifactorial properties such as antioxidant, anti-inflammatory and antidiabetic. Male infertility is one of the major health problems in life. The aim of this study was to investigate the effects of longterm cinnamon bark oil (CBO) ingestion on testicular antioxidant values, apoptotic germ cell and sperm quality of adult rats. Twelve male healthy Wistar rats were divided into two groups, each group containing six rats. While olive oil was given to control group, 100 mg kg 1 CBO was administered to the other group by gavage daily for 10 weeks. Body and reproductive organ weights, sperm characteristics, testicular lipid peroxidation and antioxidant enzyme activities, and testicular apoptosis via terminal deoxynucleotidyl transferase–mediated dUTP nick end labelling (TUNEL) method were examined. A significant decrease in malondialdehyde level and marked increases in reduced glutathione level, glutathione peroxidase and catalase activities were observed in rats treated with CBO compared with the control group. CBO consumption provided a significant increase in weights of testes and epididymides, epididymal sperm concentration, sperm motility and diameter of seminiferous tubules when compared with the control group. However, CBO consumption tended to decrease the abnormal sperm rate and apoptotic germ cell count, but it did not reach statistical significance. It is concluded that CBO has improvement effect on testicular oxidant–antioxidant balance and sperm quality, and its consumption may be useful for asthenozoospermic men.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Antioxidant enzymes apoptosis cinnamon bark oil lipid peroxidation sperm characteristics